BIMBINGAN TEKNIS PADA UMKM PRODUSEN MINUMAN YOGHURT DI KOTA MALANG - Sri Rulianah; Dwina Moentamaria; Prayitno Prayitno; Khalimatus Sa’diayah (Publisher UPT P2M Politeknik Negeri Malang, 2018)
Royals Kitchen is one of the MSMEs in Malang City which produces yogurt drinks, where these MSMEs have been producing yogurt since 2 - 3 years ago after obtaining permission from DISPERINDAG Malang City. In a period of time not too long, Royals Kitchen has grown significantly in the level of sales and marketing area. However, there are many problems from the Royal Kitchen UMKM, including: 1). The production process is still manual so that it has the potential to cause product contamination and product failure, 2). The capacity of pasteurization and incubation equipment for production is limited to 5 liters while to meet consumer demand the capacity of the equipment must be at least 20 liters. 3). Product quality is less standard (less consistent), 4). Weak understanding and skills in producing a product according to GMP provisions. For this reason, through this innovative PkM activity, it is hoped that there will be a solution to the problems faced by Royals Kitchen so hat these SMEs can grow well.Some of the solutions that will be provided through these innovative PkM,include: 1). Procurement of pasteurization and incubation equipment capacity of 20-30 liters, 2). HACCP and GMP training, 3). Administrative and financial management training, 4). Promotion through print media (newspapers).The expected outcomes of the solution include: Increased production capacity, improved product quality, improved administrative and financial management systems and increased sales turnover.Some of the results of the PKM activities, include: grants for pasteurization equipment with a capacity of 20 liters, increased knowledge and skills in operating pasteurization equipment, improved knowledge of administration and business finance management.